The system of ecological-economical management in agrarian production and main directions of its implementation in Ukraine - Bahorka, Mariia; Багорка, Марія Олександрівна; Kadyrus, Iryna; Кадирус, Ірина Григорівна (Institute of Economics of the Latvian Academy of Sciences, 2020)
The ecological situation in Ukraine in recent years has deteriorated so much that now both the economic status of business entities and food security of the country depend on it. One of the most important components of the economic security in the agrarian sector is the provision of its ecological and economic components in the agro-food market. The output of domestic agricultural products on the European market today acquires a new socio-economic content, and it is necessary to change the priorities in the system of agrarian relations. That is why today there is a process of reconsidering the role of economic and environmental priorities and the obvious advantage is given to the environmentally safe development of the agrarian production. The priority place in the agrarian system should be taken by the environmental quality criterion at the national level, and the need for greening the agrarian production. It is beyond any doubt and requires an immediate search for radical ways for its global implementation. Екологічна ситуація в Україні за останні роки погіршилася настільки, що зараз і економічний статус суб’єктів господарювання, і продукти харчування від цього залежить безпека країни. Однією з найважливіших компонент економічної безпеки в аграрному секторі є забезпечення його еколого-економічної складової в агропродовольстві ринку. Випуск вітчизняної сільськогосподарської продукції на європейському ринку сьогодні набуває нового соціально-економічного змісту, і тому необхідно змінити пріоритети в системі аграрних відносин. Ось чому сьогодні відбувається процес перегляду ролі економічного і екологічного пріоритетів та очевидна перевага надається екологічно-безпечному розвитку аграрного виробництва. Пріоритетне місце в аграрній системі має зайняти критерій якості навколишнього середовища на національному рівні та потреба в екологізація аграрного виробництва. Це не викликає сумнівів і вимагає негайного пошуку радикальних шляхів його глобальної реалізації.
Система екологічно-економічного управління в аграрному виробництві та основні напрямки її впровадження в Україні
Keywords: ecological situation; екологічна ситуація; agricultural production; аграрне виробництво; quality; якість; agricultural products; сільськогосподарська продукція; ecological and economic mechanism; еколого-економічний механізм